Italy : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; Staff Statement; Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report ;, 2010)
The global crisis had a severe impact on the Italian economy despite elements of strength such as high private savings, low private indebtedness, and a resilient financial system. Executive Directors decided that the public sector wage bill should remain a key element of the consolidation strategy, and close monitoring of subnational public finances should be continued. They commended the authorities for the progress made in structural reforms but stressed that a more ambitious program of reforms needed to be pursued to address Italy's growth potential.